Hypertext video for visual studies in developing contexts - Alshabi, Elham Mohammed Kaid; Mohamed Salim, Neesa Ameera; Che Cob, Saiful Akram (College of Creative Arts, 2025)
In an era where digital aesthetics and pedagogy increasingly intersect, this research examines hypertext interactive video as a tool and artistic medium to enhance visual studies in developing countries. using Vygotsky’s sociocultural theory, this study combines interviews, case studies, and literature review, supported by fieldwork in Yemen. Hypertext video, with layered visuals, non-linear navigation, and embedded assessments, turns passive learning into active artistic inquiry and encourages critical engagement. Beyond its pedagogical promise, the medium confronts structural realities: low bandwidth, limited digital literacy, and institutional resistance. The study proposes a hybrid design framework for lowresource contexts, making hypertext video both an instructional tool and a way to broaden access to arts education. By bridging artistic cognition and digital innovation, this work contributes to contemporary discourse on interactive media, inclusive pedagogy, and the future of creative education.